2022
DOI: 10.3389/fphar.2022.869794
|View full text |Cite
|
Sign up to set email alerts
|

Ferrostatin-1 Ameliorates Liver Dysfunction via Reducing Iron in Thioacetamide-induced Acute Liver Injury in Mice

Abstract: Background and Aims: Hepatic iron overload always leads to oxidative stress, which has been found to be involved in the progression of liver disease. However, whether iron disorder is involved in acute liver disease and the further molecular mechanisms remain unclear.Methods: A mice model of acute liver injury (ALI) was established via intraperitoneal injection of thioacetamide (TAA) (250 mg/kg/day) for 3 consecutive days. Ferrostatin-1 (Fer-1) was administered intraperitoneally (2.5 μM/kg/day) starting 3 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The liver is the major extraerythrocyte storage organ for iron ( Ishizaka N et al, 2005 ). Recent studies have found that hepatic iron overload always leads to oxidative stress, which has been found to be involved in the progression of liver disease ( Jiang H et al, 2022 ). However, whether iron disorder is involved in acute liver disease and the further molecular mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the major extraerythrocyte storage organ for iron ( Ishizaka N et al, 2005 ). Recent studies have found that hepatic iron overload always leads to oxidative stress, which has been found to be involved in the progression of liver disease ( Jiang H et al, 2022 ). However, whether iron disorder is involved in acute liver disease and the further molecular mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TAA-induced hepatotoxicity rat model is known to mimic human acute or chronic liver diseases. 23,38 The hepatotoxic mechanism of TAA predominantly involves the induction of LPO, oxidative stress, and inflammation. TAA, when administered, is nontoxic; however, it undergoes a biotransformation process in the liver after 6-12 h of injection 39 and is converted into its active metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Even a single intraperitoneal dose of TAA (300-600 mg/kg in rats) triggers hepatocellular degeneration and acute centrilobular necrosis of the liver within 24 h. 22,23 Reactive metabolites of TAA cause liver necrosis and injury by covalently attaching to hepatocellular macromolecules like proteins and lipids. 22 TAA-induced acute toxicity studies are used as an ideal model to study liver regeneration as it takes significantly prolonged time (up to 96 h) required for recovery.…”
mentioning
confidence: 99%
“…Another example is that of argininosuccinate synthetase 1 (ASS1), a rate-limiting enzyme in arginine metabolism that is downregulated in a Thioacetamide (TAA)-induced liver injury model [ 32 ]. TAA triggers the onset of acute liver inflammation and oxidative stress by mimicking the pathological process of liver injury [ 33 ]. The activation of the Farnesoid X receptor (FXR), an upstream transcription factor of ASS1, can directly promote ASS1 transcription and enhance arginine synthesis, leading to the alleviation of TAA-mediated liver injury [ 32 ].…”
Section: Discussionmentioning
confidence: 99%